LEGAL ASPECT OF ‘GOLD FARMING’ ISLAMIC BANKING PRODUCT - Ibrahim Siregar (Universitas Islam Negeri Jakarta, 2014)
Legal Aspects of ‘Gold Farming’ Islamic Banking Product. Islamic banking can progress quickly through market-based product innovation. This product innovation must be in accordance with the rules laid down in Islamic law. The concept of contract in Islam should pay attention to three aspects, namely: the substance of contract law, the law that is related to the substance of the contract, and contract clarity. A contract becomes invalid if ta’alluq(dependence between two or more contracts) and shafqatayn fî al-shafqah(uncertainty arising from multiple contracts) occurs. This article explains that the ‘gold farming’ products offered by Islamic bank violate of the principles of contract in Islam. This product should be the modified further to accord with the rules of Islamic contract.DOI: 10.15408/ajis.v14i2.1275